UPAYA PENURUNAN UNMET NEED MELALUI INTERVENSI LANGSUNG TERHADAP PASANGAN USIA SUBUR DAN PROVIDER DI PROVINSI BALI - Marhaeni, A.A.I.N (PIRAMIDA; Vol. 2, No. 1 Juli 2006, 2012)
Unmet need is a phenomenon that must be seriously handled by the relevant institutions. High proportion of unmet need can occur due to some factors, such as fear of side effect of contraception, lack of understanding of various contraception means as well as unaffordable charge of birth control services. This phenomenon would affect the decrease in contraception use prevalence and the increase of probability of giving a birth to unexpected children. The proportion of unmet need can be reduced by direct intervention to eligible couples that is classified as unmet need. The purpose of this study are (1) to find out internal and external factors that motivate unmet need eligible couples willing to use contraception means after the intervention done, and (2) to identify the implementation of socialization and intervention model for unmet need eligible couples. Socialization and intervention activities are conducted in five regencies (Badung, Gianyar, Karangasem, Buleleng, and Jembrana). In each regency two sub-districts are chosen, and from each sub-district two villages are selected for implementing the activities. The results show that there are 16 variables of internal factors motivating unmet need eligible couples to use contraception means after the socialization take place. This variables relate to the availability of and satisfaction to service program information, and ability to serve in explaining the program. The main external factor relates to the free charge of program services, including cost of contraception means and the installment. Implementation of socialization and intervention is conducted in 8 steps, starting from registering unmet need eligible couples to the evaluation stage. Recommendation from this study includes periodical registration of unmet need eligible couples, commitment establishment of related institutions and providers in handling unmet need, and continuous unmet need handling program.
Keywords: unmet need, intervention, provider